MUSICALITY AS ELEMENT OF DRAMATURGIC THOUGHT OF OLEKSANDR OLES - Oleksiuk, H. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
It was investigated functionality of music elements in Oleksandr Oles’s dramatical pieces. By the example of dramatic etudes of “Quiet Evening” and “Golden Thread” author, it is proved that musicality is a necessary ingredient of artistic (dramatic) thought of the writer, and the whole range of music elements contribute to indepth characteristics of heroes images, the development of the action and the conflict.